PRESERVATION OF MANUSCRIPTS BY KH IBRAHIM AL GHAZALI USING URAUCHI TECHNIQUES AT THE AL GHAZALI MOSQUE POLOREJO PONOROGO - Fitriawan, Fuad; Ulfa, Risa Alfiyah; Samsudin, S. (Jurnal 'Ulwan, 2025)
This research was carried out with the aim of finding out the preservation process and obstacles to ancient manuscripts by KH Ibrahim Al Ghazali using the urauchi technique at the Al - Ghazali Mosque in Polorejo, Ponorogo Regency. This research uses descriptive research with qualitative methods, starting from identifying ancient manuscripts one by one until the urauchi technique process is completed. The result of this research is that the preservation of the manuscript by KH Ibrahim Al-Ghazali is carried out by identifying the name of the manuscript and carrying out maintenance using the Urauchi technique, namely cleaning the manuscript from dust and fungus, then carrying out maintenance patching process and finally store it in an anti-fungal and acid box Obstacles in preserving KH Ibrahim Al-Ghazali's mushaf include many works that have not been identified and are still scattered, it takes a very long time to preserve and care for the mushaf and the filling process cannot be carried out because there is no permission from the authorities Dzuriyyah and it is still difficult to find it washi paper.